Perbandingan Teknik Pengkodean Langsung dan Tidak Langsung Pada Kasus Penjadwalan Jobshop - Rathomi, Muhamad Radzi (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2017)
Development of technology help human life in problem solving. Scheduling is a one of the problem which could be solved with it. In scheduling research, jobshop case is frequently used to test the scheduling problem solving algorithm. This study provide the comparison between direct encoding and indirect encoding approach. These approach are choices in jobshop secheduling problem research. The apparent differences of these approach are in used technique. Genetic algorithm is used as the testing algorithm. The Cases which will be used are the common cases from OR-Lib. The testing is done by looking the makespan, processing time, and objective value transformation. Testing result shows the direct encoding approach found more small makespan. Whereas indirect encoding approach can found optimal makespan in running with large number of generation.